Embryos and embryonic stem cells from the white rhinoceros - Hildebrandt, Thomas B; Hermes, Robert; Colleoni, Silvia; Diecke, Sebastian; Holtze, Susanne; Renfree, Marilyn B; Stejskal, Jan; Hayashi, Katsuhiko; Drukker, Micha; Loi, Pasqualino; Göritz, Frank; Lazzari, Giovanna; et al. (Nature communications, 2018)
The northern white rhinoceros (NWR, Ceratotherium simum cottoni) is the most endangered mammal in the world with only two females surviving. Here we adapt existing assisted reproduction techniques (ART) to fertilize Southern White Rhinoceros (SWR) oocytes with NWR spermatozoa. We show that rhinoceros oocytes can be repeatedly recovered from live SWR females by transrectal ovum pick-up, matured, fertilized by intracytoplasmic sperm injection and developed to the blastocyst stage in vitro. Next, we generate hybrid rhinoceros embryos in vitro using gametes of NWR and SWR. We also establish embryonic stem cell lines from the SWR blastocysts. Blastocysts are cryopreserved for later embryo transfer. Our results indicate that ART could be a viable strategy to rescue genes from the iconic, almost extinct, northern white rhinoceros and may also have broader impact if applied with similar success to other endangered large mammalian species.
Keywords: buněčná diferenciace; Perissodactyla; embryonální kmenové buňky; Female; Embryonic Stem Cells; zvířata; buněčné linie; Endangered Species; ženské pohlaví; Cell Line; Male; Cell Differentiation; embryo savčí; ohrožené druhy; Reproductive Techniques, Assisted; asistovaná reprodukce; Animals; mužské pohlaví; Embryo, Mammalian